2008
DOI: 10.1063/1.2976338
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the (111) twinning on the formation of diamond cubic/diamond hexagonal heterostructures in Cu-catalyzed Si nanowires

Abstract: The occurrence of heterostructures of cubic silicon/hexagonal silicon as disks defined along the nanowire ͗111͘ growth direction is reviewed in detail for Si nanowires obtained using Cu as catalyst. Detailed measurements on the structural properties of both semiconductor phases and their interface are presented. We observe that during growth, lamellar twinning on the cubic phase along the ͗111͘ direction is generated. Consecutive presence of twins along the ͗111͘ growth direction was found to be correlated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
94
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 88 publications
(103 citation statements)
references
References 63 publications
9
94
0
Order By: Relevance
“…The existence of such twins and even more extended hexagonal regions has been observed in previous works on 111 twinning on Si NWs grown by using Cu as catalyst as well as in III-V nanowires [11,12,34]. The existence of highly periodical and twinned regions leads to the formation of a local hexagonal structure.…”
Section: Effect Of the Catalyst Thicknessmentioning
confidence: 77%
See 1 more Smart Citation
“…The existence of such twins and even more extended hexagonal regions has been observed in previous works on 111 twinning on Si NWs grown by using Cu as catalyst as well as in III-V nanowires [11,12,34]. The existence of highly periodical and twinned regions leads to the formation of a local hexagonal structure.…”
Section: Effect Of the Catalyst Thicknessmentioning
confidence: 77%
“…Silicon nanowires are especially interesting as they hold the promise of further electronics miniaturization [8,9]. It has been shown that nanometer sized silicon can crystallize in structures different from the bulk diamond one, with effects on electronic properties [10][11][12]. Moreover silicon nanowires with very small diameters are expected to have a direct band gap [13], which could transform silicon in an efficient optical emitter.…”
Section: Introductionmentioning
confidence: 99%
“…This has been attributed to various factors such as the small nanowire radii 10,11 , growth kinetics 12 , interface energies 13 and electron accumulation at the catalyst's interstitial site 14 . It is now believed that the tendency of nanowires to crystalize in WZ/LD phase may be true for group-IV semiconductors as well 15 . It has been experimentally found that Si nanowires with a radius in excess of 10 nm tend to crystalize in the LD phase 16 and a number of recent theoretical investigations have confirmed that the hexagonal LD phase is the more stable for Si nanowires exceeding certain critical dimensions [17][18][19][20] .…”
Section: Introductionmentioning
confidence: 99%
“…Random transverse twin events in Si nanowires have been demonstrated with different non-Au catalysts such as Cu [46], Al [47], Ga [48], AuAg [49], etc. The first demonstration of controlled rational generation of transverse twin boundaries in Au-catalysed Si nanowires was reported by Shin et al [50] Characteristic saw-tooth faceting in nanowire morphology, due to twin boundary formation, was observed in Si nanowires.…”
mentioning
confidence: 99%